KARAKTERISTIK ENERGI GAP (Eg) KOMPOSIT ZnO/KARBON AKTIF DARI TANDAN SAWIT(Elaeis guineensis Jack)) UNTUK APLIKASI SEL SURYA - Wati, Rahma; Fadlly, Teuku Andi; Harmawan, Tisna (Jurnal Fisika, 2019)
Characteristics energy gap (Eg) composite ZnO/activated carbon from palm bunches (Elaeis guineensis Jack) for solar cell applications have been made. Zinc Oxide or ZnO is an n-type semiconductor having an Eg of 3.37 eV. This is an alternative material that attracts attention to be applied to solar cell devices. Commercial ZnO powder is used and activated carbon from Empty Fruit Bunch (TKS). The formation of activated carbon from the TKS was carried out by chemical activation and carbonization methods at 600 Â° C for 1 hour. Composite ZnO / activated carbon from TKS will be done by the method of solid state. Variations in activated carbon from the TKS varied 0, 15, 30, 45 wt.%. The composite was tested by Uv-Vis to produce a graph (hvÎ±) Â½ vs hv (eV). The graph gives the characteristics of Eg ZnO / activated carbon composite by Tauc, s plot method. The results produced the lowest Eg in the ZnO / C 45 wt.% Composite, which was 3.20 eV. Increasing activated carbon in ZnO / activated carbon composites decreases the value of Eg.Â